(untitled) (Journal of actual problems of jurisprudence, 2018)
To date, all the processes of political, economic and social reforms in the country focused on the need to address a single complex task – ensuring national security. Crucial to the execution of this complex problem is to curb the activities of the uncontrolled growth of crime, adverse changes in its structure and formation of relevant trends. Only the scientific methodology of complex systems research problems in the functioning mechanism for combating crime, can provide the necessary knowledge about these phenomena and to ensure the widespread introduction of the results into practice. The need for effective enforcement of constitutional rights and freedoms of man and citizen, redefining the role and place of fighting crime in the state mechanism, its external and internal architectonics, insufficient elaboration of relevant theoretical positions, there are a number of organizational and legal problems in the application of the law stipulate the relevance of research and development problems of the mechanism combating crime. Key words: crime, the mechanism of counteraction, crime, criminology.